2017
DOI: 10.3389/fpsyg.2017.01489
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Neural Correlates of Emotion–Cognition Interaction Using an Affective Stroop Task

Abstract: The human brain has the capacity to integrate various sources of information and continuously adapts our behavior according to situational needs in order to allow a healthy functioning. Emotion–cognition interactions are a key example for such integrative processing. However, the neuronal correlates investigating the effects of emotion on cognition remain to be explored and replication studies are needed. Previous neuroimaging studies have indicated an involvement of emotion and cognition related brain structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…We applied an affective number Stroop task as previously described in Raschle et al (2017) ( Figure 1 ). Each trial started with an emotional stimulus, i.e., a negative (Neg) or neutral (Neu) stimulus (150 ms), followed by a task trial (congruent/incongruent/neutral Stroop trial or a blank screen) and finally a relaxation period, i.e., blank screen (350 ms).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied an affective number Stroop task as previously described in Raschle et al (2017) ( Figure 1 ). Each trial started with an emotional stimulus, i.e., a negative (Neg) or neutral (Neu) stimulus (150 ms), followed by a task trial (congruent/incongruent/neutral Stroop trial or a blank screen) and finally a relaxation period, i.e., blank screen (350 ms).…”
Section: Methodsmentioning
confidence: 99%
“…The number of items was either congruent (C; e.g., number 3 in an array of 3) or incongruent (IC; e.g., number 1 in an array of 2) with the digits presented. Star shaped stimuli (S; as a neutral baseline counting condition) and blank trials (B; no response expected from participants) were used as control conditions (for further details see Raschle et al, 2017 ). Trial order and interstimulus intervals (which were 350–1850 ms) were randomized using Optseq 1 and kept constant across participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential reason for the greater prefrontal activity increase during life-worldly communication is the effect of emotions. Studies on prefrontal activity and emotions have suggested that positive emotions activate cognitive functioning (e.g., in the PFC or insula) ( Raschle et al, 2017 ), negative emotions reduce PFC activity ( Aoki et al, 2013 ), anxiety reduces the hemodynamics of right PFC lateralization ( Tseng et al, 2018 ), pleasant feelings amplify dorsolateral prefrontal cortex activity ( Perlstein et al, 2002 ), and emotions and cognition interact to control thinking and behavior ( Gray et al, 2002 ). In life-worldly communication, subjects choose topics that interest or concern them.…”
Section: Discussionmentioning
confidence: 99%
“…Salient elements of a message may attract attention to the extent of reducing adolescents’ available processing capacity to comprehend the message and remember it and its persuasiveness. It seems possible that this could be explained by a fundamental competition between emotion and cognition for neural resources because they share some neural networks [62]. This is particularly true if negative emotional images are followed by increasing cognitive demand, a sequence likely to occur in health information websites.…”
Section: Discussionmentioning
confidence: 99%